Pediatric literature shift: Growth of meta-analyses was 23 times greater than growth of randomized trials - Niforatos, Joshua D.; Chaitoff, Alexander; Weaver, Matt; Feinstein, Max M.; Johansen, Michael E. (Journal of clinical epidemiology, 2020)
To identify pediatric age groups, medical subject headings (MeSH) categories for “Child”, “Infant”, and “Adolescent” were used with Boolean operators (Fig. 1). Across clinical topic areas for “Infant” RCTs, gastroenterology/hepatology, cardiology, pulmonary medicine, neurology, and obstetrics/gynecology had more yearly publications compared to other specialties, whereas psychiatry and neurology had substantially more RCTs for “Children” (Fig. 2A–B). Efforts to mandate trial reporting, to address barriers to high-quality research, and to ensure focus on RCTs to inform appropriate SRMAs require further attention.CRediT authorship contribution statement Joshua D. Niforatos: Conceptualization, Formal analysis, Investigation, Methodology, Project administration, Writing - original draft, Writing - review & editing.